Vulnerability to Infarction During Cerebral Ischemia in Migraine Sufferers. Issue 3 (March 2018) - Pezzini, Alessandro; Busto, Giorgio; Zedde, Marialuisa; Gamba, Massimo; Zini, Andrea; Poli, Loris; Caria, Filomena; De Giuli, Valeria; Simone, Anna Maria; Pascarella, Rosario; Padovani, Alessandro; Padroni, Marina; et al.
Abstract : Background and Purpose—: Cerebral hyperexcitability in migraine experiencers might sensitize brain tissue to ischemia. We investigated whether a personal history of migraine is associated with vulnerability to brain ischemia in humans. Methods—: Multicenter cohort study of patients with acute ischemic stroke who underwent a brain computed tomography perfusion and were scheduled to undergo reperfusion therapy. In a case–control design, we compared the proportion of subjects with no-mismatch, the volume of penumbra salvaged, as well as the final infarct size in a group of patients with migraine and a group of patients with no history of migraine. Results—: We included 61 patients with migraine (34 [55.7%] men; mean age, 52.2±15.1 years; migraine without aura/migraine with aura, 44/17) and 61 patients with no history of migraine. The proportion of no-mismatch among migraineurs was significantly higher than among nonmigraineurs (17 [27.9%] versus 7 [11.5%]; P =0.039) and was more prominent among patients with migraine with aura (6 [35.3%]; P =0.030) while it was nonsignificantly increased in patients with migraine without aura (11 [25.0%]; P =0.114). Migraine, especially migraine with aura, was independently associated with a no-mismatch pattern (odds ratio, 2.65; 95% CI, 0.95–7.41 for migraine; odds ratio, 5.54; 95% CI, 1.28–23.99 for migraine with aura), and there was a linear decrease of the proportion of patients with migraine with aura with increasing quartiles of mismatch volumes. Patients with migraine with aura had also smaller volumes of salvaged penumbra (9.8±41.2 mL) compared with patients with migraine without aura (36.4±54.1 mL) and patients with no migraine (45.1±55.0 mL; P =0.056). Conversely, there was no difference in final infarct size among the 3 migraine subgroups ( P =0.312). Conclusions—: Migraine is likely to increase individual vulnerability to ischemic stroke during the process of acute brain ischemia and might represent, therefore, a potential new therapeutic target against occurrence and progression of the ischemic damage. Abstract : Supplemental Digital Content is available in the text.